Identification of 14‐3‐3zeta associated protein networks in oral cancer. Issue 7 (17th March 2016) - Matta, Ajay; Masui, Olena; Siu, K. W. Michael; Ralhan, Ranju
Abstract : Advancements in genomics, proteomics, and bioinformatics have improved our understanding of gene/protein networks involved in intra‐ and intercellular communication and tumor–host interactions. Using proteomics integrated with bioinformatics, previously we reported overexpression of 14‐3‐3ζ in premalignant oral lesions and oral squamous cell carcinoma tissues in comparison with normal oral epithelium. 14‐3‐3ζ emerged as a novel molecular target for therapeutics and a potential prognostic marker in oral squamous cell carcinoma patients. However, the role of 14‐3‐3ζ in development and progression of oral cancer is not known yet. This study aimed to identify the 14‐3‐3ζ associated protein networks in oral cancer cell lines using IP–MS/MS and bioinformatics. A total of 287 binding partners of 14‐3‐3ζ were identified in metastatic (MDA1986) and nonmetastatic (SCC4) oral cancer cell lines including other 14‐3‐3 isoforms (2%), proteins involved in apoptosis (2%), cytoskeleton (9%), metabolism (16%), and maintenance of redox potential (2%). Our bioinformatics analysis revealed involvement of 14‐3‐3ζ in protein networks regulating cell cycle, proliferation, apoptosis, cellular trafficking, and endocytosis in oral cancer. In conclusion, our data revealed several novel protein interaction networks involving 14‐3‐3ζ in oral cancer progression and metastasis.